A challenging diagnosis: Lesson from case series of sacral Ewing sarcoma. (May 2022) - Kamal, Achmad Fauzi; Cahayadi, Sigit Daru; Shihab, Reza Abidin; Ramang, Didi Saputra
Abstract: Background: Ewing's sarcoma is an aggressive bone and the surrounding soft tissue cancer primarily found in children and young adults. It is mostly observed in the trunk and long bones while unusually seen in the sacrum. Sacral Ewing sarcoma has a unique anatomic limitation due to neurological structures, vertebral column, and pelvic involvement. Hence, identifying sacral Ewing's sarcoma remains a challenge. Method: This is a case series including three patients diagnosed with Sacral Ewing's sarcoma. These three cases have been diagnosed based on clinical and radiographic examination, MRI, histopathology, and immunohistochemistry examination. Discussion: Sacral Ewing's sarcoma remains a challenge to diagnose due to its unique anatomy site. MRI examination is sensitive to detect lesions but nonspecific. Thus, require histopathological confirmation. Conclusion: Early diagnosis of Ewing's sarcoma is essential and we need to perform further examinations, such as immunohistochemistry examination, to confirm the diagnosis of Ewing's sarcoma. Highlights: Sacral Ewing's sarcoma remains a challenge to diagnose due to its unique anatomy site. MRI examination is sensitive to detect lesions but nonspecific. We recommended to perform further examinations, such as immunohistochemistry examination, to confirm the diagnosis of Ewing's sarcoma.